2016
DOI: 10.18203/2349-3259.ijct20162793
|View full text |Cite
|
Sign up to set email alerts
|

Results of a nine month home-based physical activity intervention for people living with HIV

Abstract: <p class="abstract"><strong>Background:</strong> The purpose of this investigation was to test the feasibility of a home-based moderate-intensity physical activity (MPA) program for people living with HIV/AIDS (PLWHA) currently taking antiretroviral therapy (ART).</p><p class="abstract"><strong>Methods:</strong> 68 participants recruited for a 9-month home-based PA intervention aimed to reduce risk factors of cardiovascular disease for PLWHA taking ART. All participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…Jaggers et al (2016) conducted a 9-month clinical trial of a home-based exercise intervention that incorporated self-monitoring, exercise equipment, and telephone behavioral counselling. 65 The intervention did not increase MVPA among PLHIV, and they concluded that a home-based exercise approach with coaching might not be feasible for increase physical activity in this population. Additionally, Couterno et al (2016) enrolled PLHIV in a supervised 4x/week aerobic and resistance training program in a community-based center (designed to overcome barriers of access) and found that 55% of participants did not comply with the moderate-to-vigorous exercise program.…”
Section: Discussionmentioning
confidence: 97%
“…Jaggers et al (2016) conducted a 9-month clinical trial of a home-based exercise intervention that incorporated self-monitoring, exercise equipment, and telephone behavioral counselling. 65 The intervention did not increase MVPA among PLHIV, and they concluded that a home-based exercise approach with coaching might not be feasible for increase physical activity in this population. Additionally, Couterno et al (2016) enrolled PLHIV in a supervised 4x/week aerobic and resistance training program in a community-based center (designed to overcome barriers of access) and found that 55% of participants did not comply with the moderate-to-vigorous exercise program.…”
Section: Discussionmentioning
confidence: 97%
“…23 Researchers continue to seek out solutions to this problem through interventions designed to change behaviors that promote increased physical activity in PLWH. 2426 …”
Section: Fatigue In People Living With Hivmentioning
confidence: 99%
“…Persons of low SES are more likely to travel on foot than others (Titheridge, Christie, Mackett, Oviedo Hernandez, & Ye, 2014). However, Jaggers et al (2016) conducted a 9-month home-based physical activity intervention among PLWHA and reported no significant differences in steps per day.…”
Section: Discussionmentioning
confidence: 99%